Making the Whole Greater than the Sum the Parts : A Review of Fiscal Decentralization in Vietnam - World Bank (World Bank, Hanoi, 2016)
This report provides a review of fiscal decentralization policies in Vietnam and their impact on the Government’s development objectives. It aims to inform reform of central-local fiscal relations in Vietnam to further promote growth and poverty reduction. The State Budget Law 2002 (SBL 2002) has enabled decentralization of important fiscal responsibilities to local authorities over the past ten years. This report responds to demands for more analysis of fiscal decentralization policies in Vietnam and the extent to which these have delivered on their stability, equity and efficiency objectives. It aims to inform future changes to the system of intergovernmental fiscal relations through revisions to the SBL 2002 and adoption of 2016-2020 Stability Period regulations. This report builds on existing research and aims to provide new analysis and perspectives on the above areas through extensive study of available data, consultations with central and local authorities, and reviews of laws, regulations and policies at central and local levels. It covers the following five pillars of fiscal decentralization: (i) expenditure decentralization and accountability; (ii) expenditure performance of local authorities; (iii) local revenue arrangements; (iv) intergovernmental fiscal transfers; and (v) local borrowing.